2008
DOI: 10.1590/s1519-566x2008000300011
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de meios de cultura na virulência de Hirsutella thompsonii (Fischer) (Deuteromycetes) para o controle Brevipalpus phoenicis (Geijskes) (Acari: Tenuipalpidae)

Abstract: The virulence of Hirsutella thompsonii (Fischer) to Brevipalpus phoenicis (Geijskes) was evaluated in laboratory, grown on complete and solid culture media (MC-S); complete and liquid culture media (MC-L); rice (APC) and powdered rice (APC-SM). Adults were confined to arenas prepared with citrus leaves in acrylic dishes containing water-agar. Conidial suspensions were prepared at different concentration (3.2 x 10(5) to 1 x 10(7) spores/ml) and applied on mites to establish the table curve-response on fourth da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Fungicide resistance to fenbuconazole and triphenyltin hydroxide was also observed in B. bassiana following selection on solid media (thereby conÞrming results of Shapiro-Ilan et al [2002]), yet in liquid media resistance was only detected in fenbuconazole. Previous studies also indicated differential effects of media (e.g., liquid vs. solid or other media components) on B. bassiana (Rodriguez-Gomez et al 2009) and Hirsutella thompsonii (Fischer) (Rossi-Zalaf et al 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Fungicide resistance to fenbuconazole and triphenyltin hydroxide was also observed in B. bassiana following selection on solid media (thereby conÞrming results of Shapiro-Ilan et al [2002]), yet in liquid media resistance was only detected in fenbuconazole. Previous studies also indicated differential effects of media (e.g., liquid vs. solid or other media components) on B. bassiana (Rodriguez-Gomez et al 2009) and Hirsutella thompsonii (Fischer) (Rossi-Zalaf et al 2008).…”
Section: Discussionmentioning
confidence: 93%